2021
DOI: 10.2298/jsc200521044o
|View full text |Cite
|
Sign up to set email alerts
|

Density functional theory calculation of propane cracking mechanism over chromium (III) oxide by cluster approach

Abstract: The catalyst coking and production of undesired products during the transformation of propane into propylene has been in a critical challenge in the on-purpose approach of propylene production. The mechanism contributing to this challenge was theoretically investigated through the investigation of cracking reaction routes to understanding how to promote the coking of this catalyst. The study carried out employed the use of a DFT and cluster approach in the search for the kinetic and thermodyn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 25 publications
1
5
0
Order By: Relevance
“…The rate-determining step (RDS) obtained in this study was found to be similar to that which was identified by Oyegoke et al [17], for the cracking of propane into small molecules, although the reaction path is different (Cr-O is feasible for propane dehydrogenation while Cr-Cr route is feasible for propane cracking). The energy barrier obtained for the second C-H abstraction step in this study was found to be lower than that barrier obtained by Oyegoke et al [17] for the cracking of propyl specie on the path of Cr-Cr reaction route, which often leads to cracking of the molecule due to the high activity of the Cr sites present on the catalyst surface in agreement with literature [10]. Therefore, this suggests reducing Cr site dominance on the catalyst surface via the substitution of selected Cr sites or oxidant/oxygen use.…”
Section: Evaluation Of Thermodynamic Feasibility Of a Different Reactsupporting
confidence: 85%
See 2 more Smart Citations
“…The rate-determining step (RDS) obtained in this study was found to be similar to that which was identified by Oyegoke et al [17], for the cracking of propane into small molecules, although the reaction path is different (Cr-O is feasible for propane dehydrogenation while Cr-Cr route is feasible for propane cracking). The energy barrier obtained for the second C-H abstraction step in this study was found to be lower than that barrier obtained by Oyegoke et al [17] for the cracking of propyl specie on the path of Cr-Cr reaction route, which often leads to cracking of the molecule due to the high activity of the Cr sites present on the catalyst surface in agreement with literature [10]. Therefore, this suggests reducing Cr site dominance on the catalyst surface via the substitution of selected Cr sites or oxidant/oxygen use.…”
Section: Evaluation Of Thermodynamic Feasibility Of a Different Reactsupporting
confidence: 85%
“…Similarly, the findings agreed with the report of Oyegoke et al [10] on the chromium oxide sites' acidity reactivity, where Cr site was confirmed to be the most active site on a chromium oxide catalyst. However, an excess concentration of these Cr sites would tend to promote the cracking of the propane into undesired products as reported in the literature [17] where the Cr-Cr reaction route was identified to be the path promoting cracking of propane into smaller molecules (methane, ethylene, and cokes) which could lead to coking of the catalyst. Figures 5 and 6 show the reaction energies for the forward reactions of the elementary steps in the propane dehydrogenation process.…”
Section: Reaction Steps Reaction Stepsmentioning
confidence: 79%
See 1 more Smart Citation
“…However, the literature shows that studies were primarily concentrating their investigations on using platinum-based catalysts. [8][9][10][11][12][13][14][15][16][17][18] Only a few studies gave preferential attention to chromium-based catalysts, [19][20][21][22][23][24][25][26][27][28][29][30][31][32] while some have investigated other catalyst forms like zeolite, nickel, gallium oxide, and many others. [33][34][35][36] Existing reports show that some works deployed an experimental approach to study the catalysts.…”
Section: Introductionmentioning
confidence: 99%
“…Among the few studies that have reported on the use of chromium-based catalysts is the report of Oyegoke et al, 28 which indicated that the chromium site played a significant role in controlling the reaction compared to the oxygen site on the Cr 2 O 3 catalyst. Another report 29 showed that highly concentrated chromium sites on the chromium-based catalyst can promote deeper dehydrogenation, cracking the intermediates to undesired products. It was further reported that the reaction paths with moderate chromium site participation favoured better selectivity for propylene production.…”
Section: Introductionmentioning
confidence: 99%